A new classification of clock Synchronization in Wireless Sensor Networks - Habib Aissaoua; Makhlouf Aliouat; Abdelkader Laouid; Farid Lalem (University of Eloued, 2019)
Since the birth of computer networks and distributed systems, the clock synchronization issue has been considered as a major challenge. In fact, the importance to have clocks synchronized resides in the fact that a wide range of communication protocols and applications necessitate a common notion of time for the overall network nodes to operate perfectly. MAC protocols and node sleep scheduling are protocol examples based on synchronized clocks. The design of synchronization protocols is challenged by the uncertainty arising from message latency and clock drifting, and also by resource constrained nodes. In this work, we first exhibit the basic concepts of the clock synchronization issue, and we provide a thorough classification based on the features that have to be considered when designing synchronization protocols in such networks
Intervention
Keywords: Wireless Sensor Networks; Clock synchronization; Time drift; Message delay uncertainty; Accuracy